Effects of Zingiber officinale Aqueous Extract on Semen Characteristic and Some Blood Plasma, Semen Plasma Parameters in the Broilers Breeder Male - Saeid, J.M.; Shanoon, A.K.; Marbut, M.M. (International Journal of Poultry Science, 2011)
To investigate the effects of Zingiber Officinale on male reproductive functions and study the mechanisms underlying these effects, aqueous extract of Zingiber officinale were administered in drinking water to two groups of male broilers breeder (24wk age) at 5% and 10%. A third group served as control and received the treatment vehicle, distilled water. Treatment lasted for 28, 32, 36, 40 and 44 wk age. Ejaculate volume, sperm concentration, counts, movements, motility and abnormality, semen plasma cholesterol, protein and glucose, the antioxidant malonhydialdehyde, glutathione and blood serum LH, FSH and testosterone, were determined. The treatment caused a significant increase (p